Relevant Soft Skils Required By Business Education Students For Enhancing Employability - Owenvbiugie, Robinson Osarumwense (International Journal of Management and Digital Business, 2022)
Relevant soft skills possessed by business education graduates for employability was examined. Three research questions and one hypothesis gave credence to the study. A population of 1117 entrepreneurs was used. The sample size was 264 entrepreneurs representing 23.63% of the population. Descriptive survey was used. The questionnaire was validated by three business educators. A reliability of 0.80 was obtained with the aid of Cronbach alpha. Arithmetic mean was used to answer the research questions. The analysis disclosed that entrepreneurs need business education graduates who possess communication, managing conflict and collaborative skills. The study also disclosed that there is no significant different between male and female graduates in the possession of skills for employability. Consequently, it was recommended that management of various universities should ensure that business education programmes are constantly reviewed in their curriculum to reflect the various skills needed for employability so as to meet competitive work environment. Business education lecturers should be trained and retrained on a continuous basis to meet with current business skills needed for employability in world of work, and frantic efforts must be made by government to equip business education laboratories and workshops to enhance effective teaching and learning of the various skills with modern and up to date equipment